Pendidikan Karakter dalam Perspektif Muhammadiyah - Kaharuddin, Saiful; Malli, Rusli; Lamabawa, Dahlan (Polyscopia, 2024)
This research analyzes the concept of character education from the perspectives of the Al-Qur'an, Muhammadiyah figures, and Muhammadiyah itself to offer comprehensive ideas about character education. Employing library research, primary sources include works by Muhammadiyah figures and other literature on character education. The findings reveal: 1) The Al-Qur'an advocates various aspects of character education, such as goodness (ihsan), virtues (al-birr), fulfilling promises (al-wafa), patience, honesty, reverence for Allah SWT, justice, and forgiveness, as seen in Surah An-Nahl verse 90 and Surah Al-Isra' verses 23-24. 2) Muhammadiyah figures like KH. Ahmad Dahlan emphasize cultivating Muslims with virtuous characters, broad perspectives, and societal commitment, while Syafi'i Ma'arif highlights the collaborative nature of character education involving educators, parents, teachers, and society. Muhammadiyah's commitment is evident through Al-Islam and Muhammadiyah (AIK) education across its institutions, aiming to develop an Indonesian society with superior traits such as being religious, moderate, intelligent, knowledgeable, independent, and cooperative.